A re-evaluation of the two-step spin crossover in the trinuclear cation [Co3(dipyridylamido)4Cl2]+. - Pantazis, D; Murillo, C; McGrady, J (2008)
Density functional theory is used to explore the electronic states involved in the remarkable two-step spin crossover (S = 0 --> S = 1 --> S = 2) in the cationic extended metal atom chain [Co(3)(dpa)(4)Cl(2)](+) (dpa = the anion of 2-dipyridylamine) (R. Clérac, F. A. Cotton, K. R. Dunbar, T. Lu, C. A. Murillo and X. Wang, J. Am. Chem. Soc., 2000, 122, 2272). The calculations are consistent with a model in which all three spin states share one common feature-a vacancy in the d(xy) orbital on the central cobalt atom which is stabilised by pi donation from four amide groups. As a result, all three can be considered to contain a Co(2+)-Co(3+)-Co(2+) chain. The singlet and triplet states arise from antiferromagnetic and ferromagnetic coupling, respectively, between the unpaired electron in this d(xy) orbital and another localised entirely on the terminal cobalt centres (the antisymmetric combination of Co d(z(2))). The singlet-triplet transition does not, therefore, populate any additional antibonding orbitals, and as a result the structure is almost invariant around the characteristic temperature of the singlet-triplet transition. In the most stable quintet, in contrast, the symmetry of the Co-Co-Co chain is broken, giving rise to a localised high-spin Co(II) centre (S = 3/2), ferromagnetically coupled to a Co(III)-Co(II) dimer (S = 1/2). The structural changes associated with this transition are apparent in the X-ray data in subtle changes in both Co-N and Co-Cl bond lengths, although their magnitude is damped by the relatively low population (18%) of the quintet even at 300 K.